الإسهام النسبي لأساليب اتخاذ القرار والمرونة المعرفية وفعالية الذات الاجتماعية في التنبؤ بالحكمة لدى طلبة الجامعة - النجار، حسني زكريا السيد (جامعة بنها - كلية التربية, 2018)
هدف البحث إلى التعرف على الإسهام النسبي لأساليب اتخاذ القرار والمرونة المعرفية وفعالية الذات الاجتماعية في التنبؤ بالحكمة لدى طلبة الجامعة والكشف عن العلاقة بينهم، وكذلك الكشف عن تأثير كل من التخصص (علمي-أدبي) والنوع (ذكور-إناث) والفرقة الدراسية (أولى-رابعة) وتفاعلاتهم في الحكمة وأساليب اتخاذ القرار وفعالية الذات الاجتماعية. تكونت عينة البحث الأساسية من (532) طالب وطالبة من كليتي التربية والعلوم بجامعة كفر الشيخ، اشتملت أدوات البحث على مقياس تطور الحكمة، ومقياس أساليب اتخاذ القرار ومقياس المرونة المعرفية ومقياس فعالية الذات الاجتماعية، اعتمد البحث على المنهج الوصفي، وباستخدام معامل الارتباط، وتحليل الانحدار المتعدد المتدرج، وتحليل التباين الثلاثي، توصلت أهم النتائج إلى: وجود علاقة ارتباطية موجبة ودالة إحصائيا بين الحكمة (الأبعاد والدرجة الكلية) وكل من أساليب اتخاذ القرار (العقلاني-الاعتمادي-التلقائي-الحدسي-التجنبي) والمرونة المعرفية، وفعالية الذات الاجتماعية الدرجة الكلية وبعد الثقة بالنفس، ولكنها كانت سالبة بين بعد المعرفة الذاتية كأحد أبعاد الحكمة وأسلوبي اتخاذ القرار (الاعتمادي-التجنبي)، وكذلك أشارت النتائج إلى أنه يمكن التنبؤ بالدرجة الكلية للحكمة من بعض أساليب اتخاذ القرار (الأسلوب العقلاني، الأسلوب الحدسي، الأسلوب التجنبي) وبعدي المرونة المعرفية (المرونة التكيفية، المرونة التلقائية) وأحد أبعاد فعالية الذات الاجتماعية (الثقة بالنفس في العلاقات الاجتماعية) لدى طلبة الجامعة. كما أشارت النتائج إلى وجود تأثير دال إحصائيا للتخصص (أدبي-علمي) في الحكمة لصالح طلاب العلمي، ووجود تأثير دال إحصائيا للنوع (ذكور-إناث) لصالح الذكور، ووجود تأثير دال إحصائيا للفرقة الدراسية (أولى-رابعة) لصالح طلاب الفرقة الرابعة الأكبر سنا، ووجود تأثير للتفاعل بين التخصص والفرقة والنوع، وعدم وجود تأثير دال إحصائيا للتفاعل سواء بين التخصص والنوع أو بين التخصص والفرقة أو بين النوع والفرقة، ووجود تأثير دال إحصائيا لكل من التخصص (علمي-أدبي) والفرقة الدراسية (أولى-رابعة) والجنس (ذكور-إناث) وتفاعلاتهم على بعض أساليب اتخاذ القرار لدى طلبة الجامعة، ووجود تأثير دال إحصائيا للتخصص (أدبي-علمي) في المرونة المعرفية لصالح طلاب العلمي، للفرقة الدراسية (أولى-رابعة) لصالح طلاب الفرقة الرابعة، وعدم وجود تأثير دال إحصائيا للنوع وكذلك للتفاعل بين التخصص والفرقة أو بين التخصص والنوع أو بين التخصص والفرقة والنوع، ووجود تأثير دال إحصائيا للتخصص (أدبي-علمي) في فعالية الذات الاجتماعية لصالح طلاب العلمي، وعدم وجود تأثير دال إحصائيا للفرقة أو النوع وكذلك عدم وجود تأثير دال إحصائيا للتفاعل في فعالية الذات الاجتماعية.
The research aims to identify the relative contribution of decision ¬making styles, cognitive flexibility and social self-efficacy in predicting the wisdom of university students and reveal the relationship between them, as well as revealing the effect of both specialization (scientific - literary) and gender (male-female) and the study year (first -fourth) and their interactions in wisdom, decision-making styles and social self- efficacy, The basic research sample consisted of (532) students from the faculties of education and sciences at Kafr ElSheikh University, The research tools included the evolution of wisdom scale, the decision¬ making styles scale, the cognitive flexibility scale and the social self- efficacy scale, The research was based on the Descriptive method. Using the correlation coefficient, the multi-gradient regression analysis, and the three ways analysis of variance, the main findings were: The existence of a positive and significant correlative relationship between wisdom (the dimensions and the total degree) and each of the decision -making styles (rational-dependence-automatic-intuitive-reactive), cognitive flexibility, Social self-efficacy (total degree) and self- confidence, but it was negative between self-cognition as one of the wisdom dimensions and the styles of decision-making (dependability- avoidance) , The results also indicate that it is possible to predict the total degree of wisdom from some decision-making styles (rationalism, intuition, avoidance), cognitive flexibility (adaptive flexibility, spontaneous flexibility) and one dimension of social self-efficacy. The results also indicated a statistically significant effect of the (literary-scientific) specialization on wisdom for students of science, and the existence of a statistically significant effect of gender (male / female) in favor of male, The existence of a statistically significant effect of the study year (first-fourth) in favor of the fourth oldest students, and the impact of interaction between specialization, study year and gender. And the absence of between specialization and gender, or between specialization and study year or between gender and study year, and the existence of a statistically significant effect on both the specialization (scientific- literary), study year (first-fourth) , gender (male-female) and their interaction on some of the decision-making styles of the university students, and the existence of a statistical effect of the specialization (literary-scientific) in the cognitive flexibility in favor of students of science, the study year (first-fourth) for the fourth year students, and the absence of a statistical effect of the gender and the interaction between specialization and study year or between the specialization and gender, or between specialization, study year and gender. There is a statistically significant effect of the specialization (literary-scientific) on social self- efficacy for science students, the absence of a statistically significant effect of the study year or gender, and the absence of a statistically significant effect of interaction in social self-efficacy.
Keywords: اتخاذ القرارات -- المرونة المعرفية -- العلاقات الإجتماعية -- طلاب الجامعات -- علم النفس التربوى